Deformation Behavior of Human Dentin under Uniaxial Compression - Dmitry Zaytsev; Sergey Grigoriev; Peter Panfilov (International Journal of Biomaterials)
Deformation behavior of a human dentin under compression including size and rate effects is studied. No difference between mechanical properties of crown and root dentin is found. It is mechanically isotropic high elastic and strong hard tissue, which demonstrates considerable plasticity and ability to suppress a crack growth. Mechanical properties of dentin depend on a shape of samples and a deformation rate.